2017
DOI: 10.1186/s12939-017-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Internalized homophobia, mental health, sexual behaviors, and outness of gay/bisexual men from Southwest China

Abstract: BackgroundSocial attitudes toward male homosexuality in China so far are still not optimistic. Sexual minorities in China have reported high levels of internalized homophobia.MethodsThis Internet-based study examined the associations among internalized homophobia, mental health, sexual behaviors, and outness among 435 gay/bisexual men in Southwest China from 2014 to 2015. Latent profile analysis, confirmatory factor analysis, univariate logistic regression, and separate multivariate logistic regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 37 publications
6
71
1
1
Order By: Relevance
“…26,27 Furthermore, they may have had fewer opportunities to develop effective coping strategies that could help them deal with mental health issues than older LGB adults. 28,29 Consistent with findings reported in studies conducted elsewhere, [4][5][6][7][8] there was a statistically significant association between IHP and depressive symptoms among Korean LGB participants. In the age-stratified analyses, IHP was associated with depressive symptoms in older LGB people, particularly LGB adults aged 40-69 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…26,27 Furthermore, they may have had fewer opportunities to develop effective coping strategies that could help them deal with mental health issues than older LGB adults. 28,29 Consistent with findings reported in studies conducted elsewhere, [4][5][6][7][8] there was a statistically significant association between IHP and depressive symptoms among Korean LGB participants. In the age-stratified analyses, IHP was associated with depressive symptoms in older LGB people, particularly LGB adults aged 40-69 years.…”
Section: Discussionsupporting
confidence: 85%
“…2,3 The literature has indicated that IHP is related to mental health problems, including depressive symptoms and suicidal behaviors. [4][5][6][7][8] A meta-analysis of 31 empirical research studies investigating the association between IHP and mental health suggested that age could be an effect modifier in the association between IHP and negative mental health outcomes. 7 The aforementioned study revealed that the association of IHP with poor mental health became stronger as the participants' age increased.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Chinese MSM experience high levels of sexual and gender minority stress. Our study indicated that the average score of internalised homophobia among our participants was significantly higher than the average scores seen in studies outside of China 24 25. Those men with internalised homophobia might believe that homosexuality is ethically wrong or psychologically abnormal, that homosexual behaviours are shameful, or that gay relationships are more likely to be unsuccessful 26.…”
Section: Discussioncontrasting
confidence: 73%
“…However, other research has documented significant relationships between mental distress and smoking among sexual minority men globally. [44][45][46][47] There might be some contextual factorssuch as tobacco-free policy in our campus-based venues, peer influences, and social or cultural norms -confounding or buffering the effect of minority stressors on cigarette use in this study population.…”
Section: Discussionmentioning
confidence: 95%